Utility of inhaled β2-agonists in reducing serum potassium levels in adult patients with hyperkalemia: A scoping review - Leonardo Arzayus-Patiño; Ashley Y. Hinojosa-Angulo; Karen A. Rodríguez-Angulo; Michelle A. Sánchez-Caicedo; Vicente Benavides-Córdoba (PLoS ONE, 2026)
Introduction Hyperkalemia is a potentially life-threatening condition that requires prompt intervention to prevent cardiac complications. While insulin and glucose administration remains a cornerstone of treatment, inhaled β2-adrenergic agonists have been proposed as a complementary or alternative strategy, particularly in emergency settings. This scoping review aimed to describe the utility of inhaled β2-agonists in lowering serum potassium levels in adult patients. Methods A scoping review was conducted following the PRISMA-ScR guidelines and the Joanna Briggs Institute methodology. Experimental studies published within the past ten years evaluating the use of inhaled β2-agonists in adult patients with hyperkalemia were included. Five studies were analyzed (three randomized controlled trials and three quasi-experimental studies), assessing dosage, route of administration, magnitude of potassium reduction, and reported adverse events. Results Most studies used nebulized salbutamol at a dose of 10 mg, with observed reductions in serum potassium ranging from 0.62 to 1.636 mEq/L, and a peak effect between 1 and 4 hours post-administration. One study also reported the use of levalbuterol. The most common adverse effects were tachycardia, dizziness, and mild hyperglycemia, all of which were clinically manageable. Efficacy was demonstrated in both patients with chronic kidney disease and in individuals with normal renal function. Conclusion Inhaled β2-agonists, particularly nebulized salbutamol, represent an effective and safe therapeutic option for the acute reduction of serum potassium in adults with hyperkalemia. Their rapid onset of action and applicability across various patient profiles make them a valuable tool in emergency settings, especially where immediate access to advanced therapies such as dialysis is limited. Further research is warranted to evaluate long-term outcomes, safety in patients with cardiovascular comorbidities, and optimal dosing strategies.